KINE[SIS]TEM’17 - Bridging Biomimetic Design and Environmental Analysis in Architecture - Oliveira, M.J. (What’s Around Design?, 2026)
Nature has always served as a model for sustainable and efficient human innovation. The Kine[SIS]tem’17 International Conference and Summer School exemplified this by integrating biomimetic principles into architectural design. The event, consisting of a two-day international conference and a nine day design studio, focused on passive, low-cost shading systems inspired by nat ural forms and processes. Keynote presentations by renowned experts—Manuel Kretzer, Alex Haw, Bob Sheil, and Alberto T. Estévez—offered interdisciplinary insights on topics such as process-oriented design, human biological responses, and adaptable architectural solutions. The design studio challenged participants to create nature-inspired shading systems for a specific site on the University cam pus. After analyzing environmental conditions, participants developed three dis tinct systems: Mechanical Leaves, The Lotus Project, and Bioshading. Mechanical Leaves employed electronically controlled units inspired by palm leaves to allow real-time shading adjustments but faced challenges with weight. The Lotus Project, drawing inspiration from the Codariocalyx motorius plant and Lotus flower, bal anced sun protection and wind regulation with aesthetics, though it struggled to fully block environmental factors. Bioshading, featuring a pyramidal structure inspired by animal pupils, responded dynamically to changes in light intensity but required complex fabrication processes. Each shading system demonstrated its own strengths and limitations, reflecting the dynamic balance between aes thetic appeal, environmental responsiveness, and practical application. Overall, Kine[SIS]tem’17 highlighted the potential of biomimetic design in addressing contemporary architectural challenges, emphasizing the importance of contextual adaptation, material considerations, and balancing innovation with functionality